Cardiac Imaging - Jeudy, Jean (A Core Review Ser., 2021)
"The second edition of the Cardiac Imaging: A Core Review builds on the success of the first edition by covering the essential aspects of cardiac imaging in a manner that serves as a guide for residents to assess their knowledge and review the material in a format that is like the ABR core examination"--